Answer: The solution to the above expression is 10.
It is not extraneous solution, as it not satisfying the equation.
Explanation:
Since we have given that
3 square root x+6 =-12
that means,
![3√(x+6)=-12](https://img.qammunity.org/2019/formulas/mathematics/high-school/eegmfw37fflyanblsklf95fcrug10kajpk.png)
We just need to find the value of x:
![3√(x+6)=-12\\\\√(x+6)=(-12)/(3)\\\\√(x+6)=-4\\\\\text{ On squaring both sides, we get}\\\\x+6=(-4)^2\\\\x+6=16\\\\x=16-6\\\\x=10](https://img.qammunity.org/2019/formulas/mathematics/high-school/metg7pr97c0ekqu1srqhfpgg1prq6hub03.png)
Hence, the solution to the above expression is 10.
Now, we have to check whether it is extraneous solution or not.
Put x= 10 in the above expression,
![3√(10+6)=-12\\\\3√(4)=-12\\\\3* 4=-12\\\\12\\eq -12](https://img.qammunity.org/2019/formulas/mathematics/high-school/y933u3b944hv8bgbp4aspwyi0k4zb1i39d.png)
Hence, it is not extraneous solution, as it not satisfying the equation.